Bacterial soft rot and top rot of sorghum caused by Bacillus subtilis in Gulbarga - and K. ASHOK KUMAR, A.H. RAJASAB, S.K. ANJANA DEVI (Indian Phytopathology, 2002)
The causal agent of a leaf blotch affecting sorghum in Gulbarga, Karnataka, India, was identified as Bacillus subtilis. B. subtilis was reisolated from symptomatic plants that had been inoculated with a suspension of the pathogen. The symptoms included blotching of the leaf sheath, reddening of the lamina, inflorescence rotting in the boot of the flag leaf and rooting at the upper 1-3 internodes.